Seroprevalence of Leptospira spp. antibodies in humans and livestock at various human-animal interfaces in Jordan - Zuhair Bani Ismail; Lea Widemann; Yasmin Daradkeh; Omar Al-Omari; Alaa Fahmawi; Mais Lakaideh; Belal Sha’fout; Haia Mellhem; Leen Al-Bayari; Saad Al-Omari; Hani Talafha; Zaidoun Hijazeen; et al. (Veterinary World)
Background and Aim: Leptospirosis, caused by Leptospira spp., affects humans and animals, posing significant health and economic burdens. This multidisciplinary One Health study aimed to estimate the prevalence of Leptospira spp.-specific antibodies in humans and livestock at the human-animal interfaces in Jordan.